QRIS ADOPTION AND UTILIZATION: EXAMINING GEN Z’S DIGITAL PAYMENT BEHAVIOR AMONG INDONESIAN VOCATIONAL STUDENTS - Andriyani, Febri; Siagian, Beatrix; Suciati, Pijar; Citra, Ajenk (Jurnal Vokasi Indonesia, 2025)
The rapid growth of digital payment systems has significantly influenced consumer behavior, particularly among Generation Z, who readily adopt cashless transactions. This study examines the adoption and usage of QRIS (Quick Response Code Indonesian Standard) as a payment method at the Vocational Education Program, Universitas Indonesia (Vokasi UI) canteen. Using a descriptive research design, data were collected from 145 respondents through a structured survey with Stratified Random Sampling to ensure representativeness. The findings reveal that 98% of respondents actively use QRIS, and 100% expressed confidence in understanding its functionality. Users rated QRIS as practical and reliable (100%) and secure (98%), reflecting strong trust and perceived effectiveness. Furthermore, 84% found QRIS highly convenient, and 88% considered it more economical than other payment options. Merchant communication also played a role, with 68% acknowledging promotional efforts by vendors. These results suggest that QRIS effectively facilitates seamless digital payments and improves the payment experience within an educational environment. However, as the study focused on a single institution, further research is needed across diverse populations to validate these findings.